Pengaruh Ukuran Pemda, Leverage dan Kinerja Keuangan terhadap IFR pada Pemda dengan Dimoderasi Opini Audit - Nufus, Shanti Rahayu Hayathun; Herwanti, Titiek; Santoso, Budi (E-Jurnal Akuntansi; Vol 29 No 3 (2019), 2019)
This study aims to provide empirically the effect of size, leverage, and financial performance on Internet Financtal Reporting (IFR) and the influence of audit opinion in relations between size, leverage and financial performance on IFR in local governments in Indonesia.  Population in this research is all District and City in Indonesia. Samples were taken by purposive sampling, 203 local governments was obtained. The results show that size and financial performance has a positive and significant effect on IFR, leverage has a positive but not significant effect on IFR. Audit opinion has a positive but not significant effect to the relationship between size with the IFR, audit opinion has a negative but not significant effect on the relationship between leverage and financial performance with the IFR. Keywords : Internet Financtal Reporting, Government Size, Leverage, Financial Performance, Audit Opinion.